2021
DOI: 10.1016/j.neuroimage.2021.117744
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI measure myelin? Systematic review, qualitative assessment, and meta-analysis of studies validating microstructural imaging with myelin histology

Abstract: Highlights Systematic review and meta-analysis of studies validating microstructural imaging with myelin histology. We find many MR markers are sensitive to myelin, including FA, RD, MP, MTR, Susceptibility, R1, but not MD. Formal comparisons between MRI-based myelin markers are limited by methodological variability, inconsistent reporting and potential for publication bias. Results emphasize the advantage of using multimodal imaging whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 206 publications
6
103
0
Order By: Relevance
“…These include, but are not limited to, exchange between water pools ( West et al, 2019 ; Kalantari et al, 2011 ; Myint and Ishima, 2009 ), magnetization transfer between free water protons and macromolecules ( West et al, 2019 ; J Zhang et al, 2015), iron content ( Birkl et al, 2019 ), internal gradients ( Washburn et al, 2008 ; Seland et al, 2004 ), and differential signal attenuation due to water diffusion in underlying compartments ( Ziener et al, 2010 ; Carney et al, 1991 ; Le Bihan et al, 1989 ), which are not considered in either the BMC-mcDESPOT formalism or the other MWF measurement methods available. The importance of these effects in a particular experiment will depend both on the specifics of the sample or subject under investigation and on the details of the pulse sequence, including the selection of parameters such as TE, TR, FA, RF pulse characteristics and gradient durations and amplitudes ( Does, 2018 ; Alonso-Ortiz et al, 2015 ; Dvorak et al, 2021 ; Levesque et al, 2010 ; Lazari and Lipp, 2021 ; Bouhrara and Bonny, 2012 ). However, it must be emphasized that multi-spin echo-based MRI sequences, namely the Carr–Purcell–Meiboom–Gill sequence or its accelerated version, the gradient and spin echo sequence, remain the reference methods for MWF mapping ( MacKay and Laule, 2016 ; Alonso-Ortiz et al, 2015 ; Piredda et al, 2021 ; Dvorak et al, 2021 ; Lazari and Lipp, 2021 ; Lee et al, 2021 ; Heath et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, but are not limited to, exchange between water pools ( West et al, 2019 ; Kalantari et al, 2011 ; Myint and Ishima, 2009 ), magnetization transfer between free water protons and macromolecules ( West et al, 2019 ; J Zhang et al, 2015), iron content ( Birkl et al, 2019 ), internal gradients ( Washburn et al, 2008 ; Seland et al, 2004 ), and differential signal attenuation due to water diffusion in underlying compartments ( Ziener et al, 2010 ; Carney et al, 1991 ; Le Bihan et al, 1989 ), which are not considered in either the BMC-mcDESPOT formalism or the other MWF measurement methods available. The importance of these effects in a particular experiment will depend both on the specifics of the sample or subject under investigation and on the details of the pulse sequence, including the selection of parameters such as TE, TR, FA, RF pulse characteristics and gradient durations and amplitudes ( Does, 2018 ; Alonso-Ortiz et al, 2015 ; Dvorak et al, 2021 ; Levesque et al, 2010 ; Lazari and Lipp, 2021 ; Bouhrara and Bonny, 2012 ). However, it must be emphasized that multi-spin echo-based MRI sequences, namely the Carr–Purcell–Meiboom–Gill sequence or its accelerated version, the gradient and spin echo sequence, remain the reference methods for MWF mapping ( MacKay and Laule, 2016 ; Alonso-Ortiz et al, 2015 ; Piredda et al, 2021 ; Dvorak et al, 2021 ; Lazari and Lipp, 2021 ; Lee et al, 2021 ; Heath et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these effects in a particular experiment will depend both on the specifics of the sample or subject under investigation and on the details of the pulse sequence, including the selection of parameters such as TE, TR, FA, RF pulse characteristics and gradient durations and amplitudes ( Does, 2018 ; Alonso-Ortiz et al, 2015 ; Dvorak et al, 2021 ; Levesque et al, 2010 ; Lazari and Lipp, 2021 ; Bouhrara and Bonny, 2012 ). However, it must be emphasized that multi-spin echo-based MRI sequences, namely the Carr–Purcell–Meiboom–Gill sequence or its accelerated version, the gradient and spin echo sequence, remain the reference methods for MWF mapping ( MacKay and Laule, 2016 ; Alonso-Ortiz et al, 2015 ; Piredda et al, 2021 ; Dvorak et al, 2021 ; Lazari and Lipp, 2021 ; Lee et al, 2021 ; Heath et al, 2018 ). This is likely due to the availability of these imaging sequences on most preclinical and clinical MRI systems, the simplicity of the signal model, and the extensive histological validation conducted over the last two decades ( Laule et al, 2006 ; Laule et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite heterogeneous reports, each of these imaging modalities present a fairly good association with the underlying histology (see Refs. 150–152 for recent review and meta-analyses) and are sensitive to cortical demyelination, remyelination, neuronal density and axonal loss and can each be applied to independently predict future disability progression in the long-term. 153 However, no consensus still exist in terms of their validity and specificity to myelin.…”
Section: Advanced Imaging Techniques Imagingmentioning
confidence: 99%
“…The same principle can be exploited to make qMRI sensitive to tissue microstructure, such as iron concentration or myelination. Recent meta analyses revealed that a majority of qMRI methods are comparably sensitive to the myelin content 30,31 , although certain parameters such as myelin water fraction (MWF, relaxometrybased) and macromolecular pool fraction (MPF, MT-based) appear to be more specific.…”
Section: Introductionmentioning
confidence: 99%